Duplex Inhibition of CO2 Corrosion in Iraqi Oilfield (University of Thi-Qar Journal for Engineering Sciences, 2011)
New method for inhibition CO2 corrosion in Iraqi oilfield was used in this work. This new method included using combination of heat treatment of steel and added Aromatic(Tetrahydronaphthalene) compounds as corrosion inhibitor in different concentration (0.05%,0.1%, 0.2%, 0.5% and 1%). The results referred that the weight loss was reduced as inhibitor concentration increased for all conditions of specimens whether, there were heat treated or not. The combination of annealing heat treatment of samples and using Aromatic compounds inhibitor offered a better corrosion resistance than the combination of quenching + tempering(Q+T) samples. The presence of inhibitor improves the corrosion resistance for annealed samples. For fully annealing, the weight loss was 5 times lesser than that for (Q+T) samples,while the weight loss of steel (as received condition) was 3 times lesser than that for (Q+T)samples.